“Unity of Religious History” and “Universal Self-Consciousness”: Leading Concepts or Mere Horizons on the Way Towards a World Theology? - Welker, Michael (Harvard theological review, 1988)
It is a familiar fact that it is difficult for revolutionary “worldviews” to gain recognition and acceptance. The most successful way to overcome this problem was termed by Hegel Aufhebung. In the ideal case envisaged by Hegel, Aufhebung says that the new “worldview,” or the theory which articulates that worldview, reconstructs within itself elements of the old perspective on the world, together with a critique of that perspective. However, the preservation of old worldviews in new theories can also take a more straightforward form. Only rarely do new worldviews emerge thoroughly developed. As a rule they continue to employ numerous leading concepts which belong to the older tradition. Only after a relatively long period of time are the old leading concepts replaced or reformulated—or, on the other hand, is the new theory withdrawn. We are well acquainted with such a course of events. But that does not prevent us from living de facto with theoretical orientations towards the world which represent mixed forms of old and new theories. We simultaneously employ new perspectives and old observations, new forms of thought and old theses. We think that we can enjoy the new cake and still eat the old one. This situation usually leads us to form an unrealistic picture of the power of the newer worldview. We fail to recognize the fact that new worldviews, as a rule, substantially overextend their credit. The dangers of granting too much credit to these new conceptions are seldom seen clearly and are often underestimated.